PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR DAN SIKAP MENGHARGAI KEGUNAAN MATEMATIKA PESERTA DIDIK KELAS X SMAN 7 PADANG TAHUN PELAJARAN 2020/2021 - Zea Zisman Usman (Jurnal Edukasi dan Penelitian Matematika, 2021)
Learning results and an attitude of appreciating the usefulness of mathematics are the goals of learning mathematics. But in reality, it was found that learning results and attitudes to appreciate the usefulness of mathematics for class X SMAN 7 Padang students in the 2020/2021 school year were still low. One exertion that can defeat these issues is to apply a model Problem Posing learning in the mathematics learning. The direction of this research was to decide whether the mathematics learning results of students who learned to use the Problem Posing learning model were superior than the mathematics learning results of students who learned to use immediate learning model in grade X students of SMAN 7 Padang and to see whether the assembling of the Problem Posing learning model to learning affects the attitude of appreciating the use of mathematics in class X SMAN 7 Padang. The kind of study used is a quasi-experimental research with a design using The Static Group Design. The study population is class X students of SMAN 7 Padang in the 2020/2021 school year. The sample class was picked utilizing the Simple Random Sampling technique, which is using a lottery system. Data collection was completed utilizing the worth of the Mid-Semester Examination and a questionnaire regarding the attitude of appreciating the usefulness of mathematics which was analyzed with the normality experiment, homogeneousity test and t experiment In accordance with the data analysis, it is seen that at the real level  = 0,05, P-value = 0.000 is obtained for data on mathematics learning results and P-value = 0.035 for data on attitudes to appreciate the usefulness of mathematics. Because P-value < , then reject . So the conclusion is that the Problem Posing learning model affects the learning results and attitudes of appreciating the use of mathematics by students, where the learning results and attitudes of appreciating the usefulness of mathematics students who study with the Problem Posing learning model are greater than those who study with direct learning model in class X SMAN 7 PadangKeywords __ Problem posing, learning results, attitude of appreciating the usefulness of mathematics